Kinetics and thermodynamics of Pb sorption onto bentonite and poly(acrylic acid)/bentonite hybrid sorbent. Issue 47 (7th October 2016) - Rafiei, Hamid R.; Shirvani, Mehran; Ogunseitan, Oladele A.
Abstract: In this work, bentonite (Bent) and poly(acrylic acid)–bentonite (PAA–Bent) hybrid were applied for the removal of Lead (Pb) from aqueous solutions. Sorption experiments were conducted under batch condition at different times, Pb concentrations, and temperatures. Equilibrium studies showed that Pb sorption data on PAA–Bent followed the Langmuir model. Both capacity and affinity of PAA–Bent and Bent for Pb retention increased with rising temperature. Maximum capacity ( q m ) of PAA–Bent for Pb sorption was 91.88 mg g −1 at 15°C which increased to 96.13 mg g −1 at 50°C. For the Bent sample, the q m values were 52.31 and 82.51 mg g −1, respectively, at 15 and 50°C. The Langmuir Pb sorption affinity parameter ( K L ) was increased from 0.12 to 2.25 L mg −1 for PAA–Bent and from 0.009 to 1.19 L mg −1 for Bent, as temperature rose from 15 to 50°C. Pseudo-first and pseudo-second-order kinetic models could best describe the time-dependent Pb sorption data by the PAA–Bent which occurred at a fast rate approaching equilibrium within 30–60 min. For the Bent sample, the Elovich model was the best fitted model to the Pb sorption data. Calculation of thermodynamic parameters including Gibbs free energy changes (Δ G° = −20.07 to −40.63 kJ mol −1 ), enthalpy change (Δ H° = 146.359 kJ mol −1 ), and entropy change (Δ S° = 578.42 J mol −1 K −1 ) showed that Pb sorption on the PAA–Bent is more spontaneous, endothermic, and favored as compared to Pb sorption process on the Bent with Δ G° = –19.51 to −30.44 kJ mol −1, Δ H° = 70.02 kJ mol −1 and Δ S° = 310.94 J mol −1 K −1 . In conclusion, the PAA–Bent hybrid sorbent can be considered as a suitable candidate for the removal of Pb from aqueous solutions.